THE EXISTENCE SPESIES OF PASSIONFLOWER (Turnera subulata J.E SM. AND Turnera ulmifolia L.) ON PALM OIL PLANT (Elaeis guineensis J.) AGAINST TO THE DIVERSITY OF ENTOMOFAG AND PHYTOPHAGE INSECTS - Hidayat, Ryan; Irsan, Chandra; Setiawan, Arum (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2018)
The research was purposed to inventory and identification types of entomofag and phytophage insects on Passionflower Flower Plants in the area of PT. South Tania Branch East Burnai I. The area of research in PT. Tania Selatan East Iango Branch I is ± 20 hectares, dominated by two species of Passionflower Flower, there are Passionflower Yellow Flower (Turnera subulata J.E SM.) and Passionflower White Flower (Turnera ulmifolia L.). Entomofag and phytophage insects were collected using d-vaccum, and sweep net in every kind of Passionflower Flowers, started July until August 2017. The identification of entomofag and phytophage insects were done in the University of Sriwijaya Postgraduate Laboratory. The results of the study were 8 orders, 34 families and 48 species on Turnera subulata plants, and 9 orders, 26 families, 36 species on Turnera ulmifolia plants. The value of diversity index from entomofag and phytophage insects in Turnera subulata were 2.912 plant and the value of diversity index from entomofag and phytophage insects in Turnera subulata plants were 2.603.